Autobiographical Memory and Vocations of Learning - Steven Weiland (Adult Education Research Conference, 2001)
This paper addresses these questions: What can be derived from current theories of autobiographical memory for understanding how individuals understand and represent their aspirations, activities, and achievements in adult learning? And, How does recent autobiography represent the role of memory in learning across the life cycle? The opening section introduces current ideas about memory, in particular how we recall the personal past. The second part of the paper explores three "vocations" in learning that depend on autobiographical memory. By vocation I mean more than simply a form of work or profession, but a conviction of fitness or suitability for a particular career, and what it requires of learning in adulthood.